Pozaszkolna edukacja prawna dorosłych a komunikacja między urzędem a obywatelem - Kowalczyk, Joanna (Studia Edukacyjne, 2020)
Interaction between the office and the citizen in each state is the only way to solve administrative cases. This article focuses on the legal education of active and potential participants in administrative interaction. This text was written from the point of view of a citizen living in an institutionalized country. The author identified areas of social life that require the implementation of specific legal education plans for adults. The article shows that properly selected methods of legal education are a prerequisite for building an effective state and civil society.